2013
DOI: 10.1002/anie.201305326
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Synthesis of Benzofurans and Coumarins from Phenols and Olefins

Abstract: Triple CH functionalization: Palladium‐catalyzed synthesis of benzofurans and coumarins by reacting phenols and unactivated olefins is described. The reaction comprises sequential CH functionalization and shows diverse functional group compatibility. Preliminary mechanistic studies shed light into the possible mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
94
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 208 publications
(96 citation statements)
references
References 132 publications
1
94
0
1
Order By: Relevance
“…A brief review of the literature revealed that several different strategies for the synthesis of the benzofuran core skeleton are known 1. Examples include McMurry coupling,1s Wittig olefination,1t Sonogashira coupling,1h and other methods 1u. The popular strategy involving a Sonogashira coupling/cyclization protocol using ethoxycarbonylethenyl‐derived 2‐halophenols and alkynes (Scheme , strategy 1) worked well for ailanthoidol,1h,1q but failed for egonol and other related compounds 1g.…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of the literature revealed that several different strategies for the synthesis of the benzofuran core skeleton are known 1. Examples include McMurry coupling,1s Wittig olefination,1t Sonogashira coupling,1h and other methods 1u. The popular strategy involving a Sonogashira coupling/cyclization protocol using ethoxycarbonylethenyl‐derived 2‐halophenols and alkynes (Scheme , strategy 1) worked well for ailanthoidol,1h,1q but failed for egonol and other related compounds 1g.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Additionally,t hey have also been frequently utilized as subunits for the construction of complex organic compounds and natural products. [14] While these protocols proved important in rapidly accessing 2-substituted fused furans with high yields,t he methods remained unsuccessful with vinylheteroarenes to produce di-heteroaryls. Recently,anumber of different synthetic routes have been articulated to afford this privileged class of molecules.…”
mentioning
confidence: 99%
“…Similar reactivity was found using simple phenols as starting materials. 70 Scheme 42. Pd(II)-catalyzed synthesis of indoles from simple anilines.…”
Section: Annulations Involving Tandem Additioncyclization Processesmentioning
confidence: 99%